Blood eosinophils in COPD: friend or foe?. Issue 1 (2nd January 2022) - Papaporfyriou, Anastasia; Bakakos, Petros; Hillas, Georgios; Papaioannou, Andriana I.; Loukides, Stelios
ABSTRACT: Introduction: The pathogenesis of chronic obstructive pulmonary disease (COPD) is highly complex and the underlying cellular and molecular mechanisms remain poorly understood. Areas Covered: COPD has been traditionally associated with neutrophilic inflammation of the bronchi, but in the last decade, studies have demonstrated that eosinophils may also migrate into the lower airways of patients with COPD and their increased numbers can be noticed during exacerbations as well as stable disease. In this review, we present clinical characteristics of eosinophilic COPD, as well as the role of eosinophils as a biomarker-guided therapy in COPD. A systematic research using the database of Pubmed up to February 2021 was performed. The terms we searched were eosinophilic inflammation, COPD, COPD phenotypes, COPD exacerbations, corticosteroids in COPD, and monoclonal antibodies in COPD. Expert Opinion: Blood eosinophil levels show strong potential as a prognostic and theragnostic biomarker in the clinical management of COPD being at the moment the most reliable biomarker. The lack of a certain cutoff value of blood eosinophils as guidance for treatment with ICS and biologic therapies and the uncertainty regarding the stability of eosinophilia and eosinophilic phenotype through the course of COPD remain as unmet dilemmas and problems.